«En engi má við skǫpum vinna»: Individual Agency and Structural Determination in Vǫlsunga Saga - Barreiro, Santiago Francisco (2021)
The purpose of this article is to analyze the relationship between decision making and contextual determination in Volsunga Saga, produced in Iceland or Norway during the 13th Century. We will show that social and kinship structures impose obligations that individuals normally accept as something inexorable. We will see that the influence of structure pressure is manifested not only in the physical qualities of the individuals, but also in their personal behavior. Our aim is to demonstrate that structural constraints are compared to the inexorability of destiny and the destructive character of greed and the doom treasure of Andvari. Finally, we will discuss how the idea of intentionality is explored in the saga and may justify certain actions that go against social expectations. It will be argued that these dynamics run parallel to the theology of intention present in the Christian thought and reflect the efforts of the saga author to insert his narrative in a wider ideological context.